Solid oxide type electrochemical cell, and solid oxide type electrochemical cell stack

The solid oxide electrochemical cell design with dual hydrogen layers enhances reaction efficiency and structural strength, addressing the challenges of hydrogen pole reactions and side reactions in high-temperature applications.

JP2025016150APending Publication Date: 2025-01-31TOSHIBA ENERGY SYST & SOLUTIONS CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023119239
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

The challenge is to enhance the hydrogen pole reactions and structural strength of solid oxide electrochemical cells, which are crucial for efficient operation in high-temperature applications like fuel cells and hydrogen production, while minimizing unfavorable side reactions.

Method used

The design incorporates a first hydrogen layer with metal and metal oxide particles for catalytic activity and a second hydrogen layer with composite particles for structural support, enhancing the electrochemical cell's strength and reducing side reactions.

Benefits of technology

This configuration improves the main reaction efficiency and suppresses side reactions, leading to higher performance and durability of the electrochemical cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016150000001_ABST
    Figure 2025016150000001_ABST
Patent Text Reader

Abstract

To provide a solid oxide type electrochemical cell enabled to improve hydrogen electrode reactivity in its main reaction and enabled to improve the strength of the hydrogen electrode functioning as a support and the strength of the cell using the same.SOLUTION: The solid oxide type electrochemical cell comprises a hydrogen electrode, a solid oxide electrolyte layer, and an oxygen electrode. In the solid oxide type electrochemical cell, a hydrogen electrode 110 comprises: a first hydrogen electrode layer disposed to contact the oxide electrolyte layer; and a second hydrogen electrode layer 112 contacting a second face of the first hydrogen electrode layer present on the opposite side of the first face thereof contacting the oxide electrolyte layer. The first hydrogen electrode layer has first metal particles and first metal oxide particles, and the second hydrogen electrode layer 112 has second metal oxide particles OX3 supporting the second metal particles M2.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to solid oxide electrochemical cells and solid oxide electrochemical cell stacks. [Background technology]

[0002] Solid oxide electrochemical cells (SOCs) are used as solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs) because their high operating temperatures (600-1000°C) allow for sufficient reaction speeds without the use of expensive precious metal catalysts. SOFCs have higher power generation efficiency than other types of fuel cells, and they produce less CO 2 Because it produces little CO2, it is expected to be a clean power generation system of the next generation. Because SOEC can produce hydrogen at a low electrolysis voltage due to its high operating temperature, it is expected to be a highly efficient hydrogen production device. In addition, because of its high operating temperature, it produces not only water vapor but also CO 2 It is also possible to electrolyze CO 2 Electrolyzer or CO 2 / H 2 It can also be operated as an O co-electrolyzer. In addition, its use as an energy storage system using SOFC / SOEC is also being considered.

[0003] SOCs used as SOFCs and SOECs have a structure in which a hydrogen electrode (SOFC: hydrogen consuming electrode, SOEC: hydrogen generating electrode) is placed on one side of a solid oxide electrolyte layer, and an oxygen electrode (SOFC: oxygen consuming electrode, SOEC: oxygen generating electrode) is placed on the other side. Both electrodes have a porous structure to allow sufficient diffusion of the reactant gas, and are electrically conductive. The electrolyte for SOCs is made of highly conductive stabilized zirconia or lanthanum-gallium oxide (LaGaO 3The cell characteristics are determined by the activity of the electrode catalyst and the resistance loss that depends on the ohmic resistance between the terminals, and the catalytic activity on the hydrogen electrode side is particularly important during the electrolytic reaction. In addition, to ensure the strength of the cell, it often has a structure in which the hydrogen electrode side is used as a support. For this reason, the hydrogen electrode is required to have the strength to support the cell, catalytic activity, electrical conductivity, and diffusibility of the reactant gas. Furthermore, in the case of CO 2 Electrolysis or CO 2 / H 2 In the case of O co-electrolysis, CO is 2 →CO+1 / 2O 2 In addition to the main reaction, the undesirable side reaction of C precipitation (CO 2 →C+O 2 or CO → C+1 / 2O 2 ) may occur.

[0004] As described above, there is a need to improve the reactivity of the hydrogen electrode, which is the main reaction in SOC, as well as the strength of the hydrogen electrode, which functions as a support, and therefore the cell strength of SOC. 2 CO is more stable than O 2 Electrolysis or CO 2 / H 2 O occurs at the hydrogen electrode of the electrolysis, CO 2 →CO+1 / 2O 2 The main reaction of isopropanol is promoted, while the undesirable side reaction of C precipitation (CO 2 →C+O 2 or CO → C+1 / 2O 2 ) is required to be suppressed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-154864 A [Patent Document 2] JP 2016-071983 A Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide a solid oxide electrochemical cell and a solid oxide electrochemical cell stack which improve the reactivity of the hydrogen electrode, which is the main reaction in SOC, and which makes it possible to increase the strength of the hydrogen electrode that functions as a support and the cell using the same. [Means for solving the problem]

[0007] A solid oxide electrochemical cell of the embodiment includes a hydrogen electrode, a solid oxide electrolyte layer, and an oxygen electrode. In the solid oxide electrochemical cell of the embodiment, the hydrogen electrode includes a first hydrogen electrode layer arranged to be in contact with the oxide electrolyte layer, and a second hydrogen electrode layer in contact with a second surface of the first hydrogen electrode layer opposite to a first surface in contact with the oxide electrolyte layer. The first hydrogen electrode layer has first metal particles and first metal oxide particles, and the second hydrogen electrode layer has second metal oxide particles supporting second metal particles. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a cross-sectional view showing a solid oxide electrochemical cell according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic configuration of a second hydrogen electrode layer of the solid oxide electrochemical cell shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the solid oxide electrochemical cell of the embodiment will be described with reference to the drawings. In each embodiment shown below, substantially the same components are given the same reference numerals, and the description thereof may be omitted. The drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each part, etc. may differ from the actual ones. In the following description, the symbol "~" indicates a range between the upper limit value and the lower limit value of each numerical value. In this case, each numerical range includes the upper limit value and the lower limit value.

[0010] FIG. 1 shows a cross section of a solid oxide electrochemical cell according to an embodiment. The solid oxide electrochemical cell shown in FIG. 1 is a hydrogen electrode-supported flat plate electrochemical cell 100, and has a laminated structure of a porous hydrogen electrode 110, a solid oxide electrolyte 120, and an oxygen electrode 130. The hydrogen electrode 110 has a first hydrogen electrode layer 110 as a hydrogen electrode active layer arranged to be in contact with the solid oxide electrolyte 120, and a second hydrogen electrode layer 112 as a hydrogen electrode support layer in contact with a second surface of the first hydrogen electrode layer 110 opposite to the first surface in contact with the solid oxide electrolyte 120. A reaction prevention layer 131 may be arranged between the solid oxide electrolyte 120 and the oxygen electrode 130.

[0011] The first hydrogen electrode layer 111 is composed of a porous layer made of a hydrogen electrode active material that causes a reaction in the hydrogen electrode 110, and specifically has gas permeability due to the skeleton of a network structure. The first hydrogen electrode layer 111 has open pores inside that are at least partially surrounded by the skeleton of the network structure, and when the electrochemical cell is used as, for example, a steam electrolysis cell, water vapor that has flowed into the open pores can be electrolyzed into oxygen ions and hydrogen.

[0012] The first hydrogen electrode layer 111 comprises a composite sintered body of first metal particles and first metal oxide particles. The first metal oxide particles are at least one oxide selected from yttrium (Y) and scandium (Sc), i.e., yttrium oxide (Y 2 O 3 ) and scandium oxide (Sc 2 O 3 ) stabilized with at least one of the following: 2 ), samarium (Sm), gadolinium (Gd), and yttrium (Y), i.e., samarium oxide (Sm 2 O 3 ), gadolinium oxide (Gd 2 O 3 ), and Y 2 O 3Ceria doped with at least one of the following: 2 ), and yttrium (Y)-doped strontium titanate (SrTiO 3 It is preferable that the material contains at least one selected from the group consisting of: Y-stabilized zirconia (YSZ) is a typical example of stabilized zirconia; Gd-doped ceria (GDC) is a typical example of doped ceria.

[0013] The first metal particles contained in the sintered body or dissolved in the first metal oxide particles and functioning as a hydrogen electrode active material preferably contain at least one selected from the group consisting of nickel (Ni), copper (Cu), iron (Fe), and cobalt (Co). The first metal particles are not limited to simple particles of the above metals, and may be alloy particles containing the above metals. In the composite sintered body constituting the first hydrogen electrode layer 111, the ratio of the first metal particles to the first metal oxide particles is preferably 45:55 to 65:35 in mass ratio.

[0014] The second hydrogen electrode layer 112 is a strength member that mainly provides the strength of the electrochemical cell 100, is made of a gas-permeable porous sintered body, and has gas passages through which reactive gases such as water vapor can flow. As shown in Fig. 2, the second hydrogen electrode layer 112 is provided with a porous sintered body PS including composite particles CP (M2 / OX2) having second metal oxide particles OX2 supporting second metal particles M2. The porous sintered body PS constituting the second hydrogen electrode layer 112 may further include third metal particles M3 and third metal oxide particles OX3.

[0015] In the porous sintered body constituting the second hydrogen electrode layer 112, the second metal particles M2 supported on the second metal oxide particles OX2 preferably contain at least one selected from the group consisting of Ni, Cu, Fe, and Co. The second metal particles M2 are not limited to simple particles of the above metals, but may also be alloy particles containing the above metals. The second metal oxide particles OX2 are preferably made of alumina (Al 2 O 3 ), magnesia (MgO), and silica (SiO 2The second metal oxide particles OX2 may be composite oxide particles containing two or more of the above-mentioned metal oxides.

[0016] The third metal particles M3 preferably contain at least one selected from the group consisting of Ni, Cu, Fe, and Co. The third metal particles M3 are not limited to simple particles of the above metals, and may be alloy particles containing the above metals. The third metal oxide particles OX3 are zirconia (ZrO 2 ), ceria doped with at least one oxide selected from Sm, Gd, and Y (CeO 2 ), and Y-doped strontium titanate (SrTiO 3 It is preferable that the compound contains at least one selected from the group consisting of:

[0017] The porous sintered body constituting the second hydrogen electrode layer 112 includes composite particles CP having second metal oxide particles OX2 supporting second metal particles M2. The second metal oxide particles OX2 include at least one of alumina, magnesia, silica, and composite oxides thereof. Since these metal oxides have high strength, the composite particles CP including the second metal oxide particles OX2 can increase the strength of the second hydrogen electrode layer 112 as a hydrogen electrode support layer. This makes it possible to increase the strength of the second hydrogen electrode layer 112 and the electrochemical cell 100 having the second hydrogen electrode layer 112. Furthermore, since the second metal oxide particles OX2 support the second metal particles M2, they have electrical conductivity. This makes it possible to obtain electrical conductivity as the second hydrogen electrode layer 112 of the electrochemical cell 100. The third metal particles M3 and the third metal oxide particles OX3 also contribute to the electrical conductivity of the second hydrogen electrode layer 112.

[0018] Furthermore, the porous sintered body constituting the second hydrogen electrode layer 112 further contains third metal particles M3 and third metal oxide particles OX3. The third metal particles M3 and the third metal oxide particles OX3 function as a hydrogen electrode active material that causes a reaction in the hydrogen electrode 110. By forming the hydrogen electrode 110 from such a second hydrogen electrode layer 112 and first hydrogen electrode layer 111, the reactivity of the hydrogen electrode 110, which is the main reaction of the electrochemical cell 100, can be increased, and the main reaction can be promoted more predominantly while the occurrence rate of undesirable side reactions can be reduced. For example, CO 2 Electrolysis or CO 2 / H 2 In the case of O co-electrolysis, CO generated at the hydrogen electrode 2 →CO+1 / 2O 2 The main reaction of isopropanol is dominated by CO, which precipitates C. 2 →C+O 2 or CO → C+1 / 2O 2 It is possible to suppress the side reactions.

[0019] In the second hydrogen electrode layer 112, the volume ratio of the composite particles CP having the second metal oxide particles OX2 supporting the second metal particles M2 is preferably in the range of 3 volume % or more and 30 volume % or less. If the volume ratio of the composite particles CP is less than 3 volume %, the strength of the second hydrogen electrode layer 112 may not be sufficiently increased. If the volume ratio of the composite particles CP exceeds 30 volume %, the reaction activity, etc. of the second hydrogen electrode layer 112 may be reduced. The volume ratio of the third metal particles M3 in the second hydrogen electrode layer 112 is preferably in the range of 30 volume % or more and 65 volume % or less. In addition, the volume ratio of the third metal oxide particles OX3 is preferably in the range of 30 volume % or more and 50 volume % or less.

[0020] The second metal particles M2 preferably have an average particle size of 20 nm or more and 200 nm or less. If the average particle size of the second metal particles M2 is less than 20 nm, there is a risk of a decrease in electrical conductivity. If the average particle size of the second metal particles M2 exceeds 200 nm, there is a risk of a decrease in control of reactivity by the hydrogen electrode 110, resulting in an increase in the rate of side reactions. The average particle size of the second metal particles M2 supported on the second metal oxide particles OX2 can be measured, for example, by observing the second metal oxide particles OX2 supporting the second metal particles M2 with a scanning electron microscope (SEM), creating an image (SEM image), and subjecting the SEM image to image processing.

[0021] The solid oxide electrolyte 120 is laminated on one side with the hydrogen electrode 110, and on the other side with the oxygen electrode 130 via a reaction prevention layer 131. The solid oxide electrolyte 4 is made of a dense solid oxide electrolyte, and is an ion conductor that passes ions such as oxygen ions but does not pass electricity. The solid oxide electrolyte 120 is made of, for example, Y 2 O 3 , Sc 2 O 3 , Yb 2 O 3 , Gd 2 O 3 , CaO, MgO, and CeO 2 and stabilized zirconia in which at least one stabilizer selected from the group consisting of Ln 1-x A x BO 3-δ (Ln is a rare earth element such as La, A is at least one element selected from Sr, Ca, Ba, etc., B is at least one element selected from Ga, Cr, Mn, Co, Fe, Ni, etc., x is 0≦x≦1, and δ is 0≦δ≦1.)

[0022] The oxygen electrode 130 is made of an oxygen electrode active material and is configured as a porous body having gas diffusibility and electronic conductivity. For example, oxygen ions (O 2- ) and the electrons (e - ) to oxygen molecules (O 2The oxygen electrode 130 can be, for example, Ln 1-x A x BO 3-δ (Ln is a rare earth element such as La, A is at least one element selected from Sr, Ca, Ba, etc., B is at least one element selected from Ga, Cr, Mn, Co, Fe, Ni, etc., x is 0≦x≦1, δ is 0≦δ≦1.) is used as a porous sintered body of perovskite oxide. 1-x Sr x )(Co 1-y Fe y )O 3-δ (LSCF) is one example.

[0023] The reaction prevention layer 131 is disposed between the solid oxide electrolyte 120 and the oxygen electrode 130 as necessary, and is a dense reaction prevention layer that prevents diffusion and reaction of elements between the solid oxide electrolyte 120 and the oxygen electrode 130.

[0024] The electrochemical cell 100 of the embodiment is constructed by sequentially stacking the second hydrogen electrode layer 112, the first hydrogen electrode layer 111, the solid oxide electrolyte 120, the reaction prevention layer 131, and the oxygen electrode 130. For example, the precursor layer of the second hydrogen electrode layer 112, the precursor layer of the first hydrogen electrode layer 111, and the solid oxide electrolyte 120 are sequentially formed and fired in this manner. The reaction prevention layer 131 and the oxygen electrode 130 are sequentially formed on the fired laminate and fired in this manner. This sintered body is fired in a reducing atmosphere. For example, metal oxide particles are used as the material for forming the first metal particles, the second metal particles, and the third metal particles in the precursor layer of the second hydrogen electrode layer 112 and the precursor layer of the first hydrogen electrode layer 111, and these are fired in a reducing atmosphere to form the metal particles, thereby producing the electrochemical cell 100.

[0025] The electrochemical cell 100 of the embodiment may be used as it is, or may be used as an electrochemical cell stack having a plurality of electrochemical cells 100 stacked together. 2 Electrolyzer, CO 2 / H 2 Among these, the electrochemical cell 100 of the embodiment is used in CO 2 Electrolysis equipment and CO 2 / H 2 Suitable for O co-electrolysis devices. EXAMPLES

[0026] Next, specific examples of the electrolytic cell according to the embodiment and the evaluation results thereof will be described.

[0027] Example 1 NiO powder and Al 2 O 3 The powders are mixed and sintered to form NiAl 2 O 4 We prepared a nickel-aluminum composite oxide represented by the formula: 2 O 3 Doped ceria (GDC10) (Gd 2 O 3 ) 0.1 (CeO 2 ) 0.9 The powder was mixed with the composite oxide particles in a mass ratio of 6:4 to obtain the composition of the first hydrogen electrode layer (hydrogen electrode substrate), and the mixture was made into a paste. The paste was then formed into a sheet to prepare a precursor for the second hydrogen electrode layer (hydrogen electrode substrate). Then, a paste containing a mixture of NiO and GDC10 was mixed with the first hydrogen electrode layer (hydrogen electrode active layer) precursor and (Y 2 O 3 ) 0.08 (ZrO 2 ) 0.92 Y so that the composition is 2 O 3 A paste containing zirconia doped with YSZ8 was applied in sequence on the second hydrogen electrode layer precursor. The second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were then fired at 1200°C to 1500°C until the layers and the spaces between the layers had sufficient strength.

[0028] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 1.

[0029] The precursor of the solid oxide electrochemical cell of Example 1 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was allowed to flow, and the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor were reduced to form the first hydrogen electrode layer and the second hydrogen electrode layer.

[0030] The hydrogen electrode output characteristic evaluation device is a device that uses a mixture of water vapor, CO, and 2 , and H 2 The solid oxide electrochemical cell was operated in SOFC, SOEC, and co-electrolysis modes by supplying a mixed gas of 10 ...

[0031] Example 2 NiO powder and MgO powder were mixed and sintered to produce nickel magnesium composite oxide represented by NiMgO. This was then pulverized to produce composite oxide particles. 2 O 3A powder of NiO-doped ceria (GDC10) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing a mixture of NiO and GDC10 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in that order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired at a temperature of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0032] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired under conditions of 900° C. or higher and 1200° C. or lower to produce a precursor of the solid oxide electrochemical cell 1 of Example 2.

[0033] The precursor of the solid oxide electrochemical cell of Example 2 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0034] Example 3 NiO powder, MgO powder, and SiO 2 The powders were mixed and sintered to obtain NiMgO-SiO 2 We prepared a nickel-magnesium-silica composite oxide represented by the formula: 2 O 3A powder of NiO-doped ceria (GDC10) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing a mixture of NiO and GDC10 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in that order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired at a temperature of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0035] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0036] The precursor of the solid oxide electrochemical cell of Example 3 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0037] Example 4 CuO powder and Al 2 O 3 The powders were mixed and sintered to form CuAl 2 O 4 The copper-aluminum composite oxide represented by the formula: 2 O 3A powder of NiO-doped ceria (GDC10) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing a mixture of NiO and GDC10 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in that order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired at a temperature of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0038] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0039] The precursor of the solid oxide electrochemical cell of Example 4 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0040] Example 5 CuO powder, MgO powder, and SiO 2 The powders were mixed and sintered to produce copper-magnesium composite oxide represented by CuMgO, which was then pulverized to produce composite oxide particles. 2 O 3A powder of NiO-doped ceria (GDC10) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing a mixture of NiO and GDC10 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in that order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired at a temperature of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0041] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0042] The precursor of the solid oxide electrochemical cell of Example 5 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0043] Example 6 CuO powder and Al 2 O 3 The powder is mixed and sintered to form CuAl 2 O 4 The copper-aluminum composite oxide represented by the formula (1) was prepared. It was then pulverized to obtain composite oxide particles. 2 O 3 ) 0.08 (ZrO 2 ) 0.92 Y so that the composition is2 O 3 A powder of NiO-doped zirconia (YSZ8) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing NiO and YSZ8 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in that order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired under conditions of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0044] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0045] The precursor of the solid oxide electrochemical cell of Example 6 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0046] Example 7 CuO powder and Al 2 O 3 The powders were mixed and sintered to form CuAl 2 O 4 We prepared a copper-aluminum composite oxide represented by the formula: 3A powder of Y-doped strontium titanate (YST) mixed in a mass ratio of 6:4 to obtain a composition of Y, and a powder of composite oxide particles were mixed to form a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. Then, a paste containing a mixture of NiO and YSZ8 as a first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as an electrolyte were formed on the second hydrogen electrode layer precursor in this order. Then, the second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired under conditions of 1200°C to 1500°C until the strength within and between each layer was sufficient.

[0047] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0048] The precursor of the solid oxide electrochemical cell of Example 7 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0049] Comparative Example 1 NiO and Gd 2 O 3A paste of powder containing NiO and GDC10 was mixed with ceria doped with NiO (GDC10) in a mass ratio of 6:4 to prepare a second hydrogen electrode layer (hydrogen electrode substrate) precursor. A paste containing a mixture of NiO and GDC10 as the first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as the electrolyte were formed on the second hydrogen electrode layer precursor in that order. The second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were fired at temperatures between 1200°C and 1500°C until the layers and spaces between the layers had sufficient strength.

[0050] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired at a temperature of 900° C. to 1200° C. to prepare a precursor of the solid oxide electrochemical cell of Example 3.

[0051] The precursor of the solid oxide electrochemical cell of Example 3 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0052] (Reference example 1) Using nickel nitrate solution, Al 2 O 3 We prepared composite oxide particles with Ni metal particles supported on the surface of the powder. Nickel oxide (NiO) and Gd 2 O 3A powder of NiO-doped ceria (GDC10) mixed in a mass ratio of 6:4 and a powder of composite oxide particles were made into a paste, and this paste was formed into a sheet to produce a second hydrogen electrode layer (hydrogen electrode substrate) precursor. A paste containing a mixture of NiO and GDC10 as the first hydrogen electrode layer (hydrogen electrode active layer) precursor and a paste containing Y-stabilized zirconia (YSZ8) as the electrolyte were formed on the second hydrogen electrode layer precursor in that order. The second hydrogen electrode layer precursor-first hydrogen electrode layer precursor-electrolyte were then fired at 1200°C to 1500°C until the layers and the spaces between the layers had sufficient strength.

[0053] A sheet of GDC10 paste was formed on the sintered laminate as a reaction prevention layer, and the laminate was fired at 1000°C to 1500°C until the layers and spaces between layers had sufficient strength. Next, La(Sr)Co(Fe)O was applied as an oxygen electrode on the reaction prevention layer. 3-δ The (LSCF) paste was formed into a sheet and fired under conditions of 900° C. or higher and 1200° C. or lower to produce a precursor of the solid oxide electrochemical cell of Reference Example 1.

[0054] The precursor of the solid oxide electrochemical cell of Reference Example 1 was placed in an output characteristic evaluation device, and dry hydrogen was flowed into the hydrogen electrode side at 700° C. or higher, while N 2 / O 2 The mixed gas was passed to reduce the first hydrogen electrode layer precursor and the second hydrogen electrode layer precursor, thereby forming the first hydrogen electrode layer and the second hydrogen electrode layer. The initial state IV characteristics were evaluated in the same manner as in Example 1 using the hydrogen electrode output characteristics evaluation device.

[0055] (Co-electrolysis characteristic evaluation / main reaction ratio measurement) The main reaction ratio was calculated from the reaction amount of the outlet gas in the co-electrolysis mode in Examples 1 to 7, Comparative Example 1, and Reference Example 1. The results are shown in Table 1. Table 1 also shows the average particle diameters of the second metal particles, the second metal oxide particles, the third metal oxide particles, and the second metal particles. The main reaction amounts of the cells in Examples 1 to 3 are almost the same, and are larger than the ratio in Comparative Example 1, so the effect of the Ni metal fine particles is well expressed. Furthermore, when comparing Example 1 and Reference Example 1, it can be seen that the average particle diameter of the metal particles in Reference Example 1 prepared by the impregnation method is 300 nm, which is larger than that in Example 1, and the side reaction suppression effect is low. In addition, when comparing Example 4 with Example 1 and Comparative Example 1, it can be seen that the main reaction amount can be increased more in Example 4, and the side reaction suppression effect is greater for Cu than Ni. Furthermore, since the main reaction amounts in Examples 4 to 7 are almost the same, all of the metal particles selected here can express the effect of Cu.

[0056] [Table 1]

[0057] The configurations of the above-mentioned embodiments can be applied in combination with each other, and some of them can be replaced. Although several embodiments of the present invention have been described here, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are also included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0058] 100...electrochemical cell, 110...hydrogen electrode, 111...first hydrogen electrode layer, 112...second hydrogen electrode layer, 120...solid oxide electrolyte, 130...oxygen electrode, 131...reaction prevention layer, M2...second metal particle, OX2...second metal oxide particle, CP(M2 / OX2)...composite particle, PS...porous sintered body, M3...third metal particle, OX3...third metal oxide particle.

Claims

1. A solid oxide electrochemical cell comprising a hydrogen electrode, a solid oxide electrolyte layer, and an oxygen electrode, the hydrogen electrode includes a first hydrogen electrode layer disposed so as to be in contact with the oxide electrolyte layer, and a second hydrogen electrode layer in contact with a second surface of the first hydrogen electrode layer opposite to a first surface in contact with the oxide electrolyte layer, the first hydrogen electrode layer includes first metal particles and first metal oxide particles; The second hydrogen electrode layer comprises second metal oxide particles supporting second metal particles.

2. 2. The solid oxide electrochemical cell of claim 1, wherein the second hydrogen electrode layer further comprises a third metal particle and a third metal oxide particle.

3. The first metal particles include at least one selected from the group consisting of Ni, Cu, Co, and Fe, and the first metal oxide particles include at least one selected from the group consisting of zirconia stabilized with at least one oxide selected from Y and Sc, ceria doped with at least one oxide selected from Sm, Gd, and Y, and strontium titanate doped with Y; 2. The solid oxide electrochemical cell of claim 1, wherein the second metal particles include at least one selected from the group consisting of Ni, Cu, Co, and Fe, and the second metal oxide particles include at least one selected from the group consisting of alumina, magnesia, and silica.

4. 3. The solid oxide electrochemical cell according to claim 2, wherein the third metal particles include at least one selected from the group consisting of Ni, Cu, Co, and Fe, and the third metal oxide particles include at least one selected from the group consisting of zirconia stabilized with at least one oxide selected from Y and Sc, ceria doped with at least one oxide selected from Sm, Gd, and Y, and strontium titanate doped with Y.

5. 2. The solid oxide electrochemical cell according to claim 1, wherein the second hydrogen electrode layer contains the second metal oxide particles supporting the second metal particles in an amount ranging from 3 vol % to 30 vol %.

6. 2. The solid oxide electrochemical cell of claim 1, wherein the second metal particles have an average particle size of 20 nm or more and 200 nm or less.

7. 10. The solid oxide electrochemical cell of claim 1, wherein the second metal particles are reduced metal oxide particles.

8. 2. The solid oxide electrochemical cell according to claim 1, wherein the solid oxide electrochemical cell is an electrolysis cell for electrolyzing carbon dioxide or an electrolysis cell for co-electrolyzing carbon dioxide and water.

9. A solid oxide electrochemical cell stack comprising a plurality of solid oxide electrochemical cells according to any one of claims 1 to 8 stacked together.

Citation Information

Patent Citations

  • Solid oxide electrochemical cell and processes for producing the same

    JP2009211830A

  • Solid oxide electrochemical cell and method for manufacturing the same

    JP2010044966A

  • Method for producing synthesis gas for use in a hydroformylation plant

    JP2020519758A

  • Solid oxide fuel cell and manufacturing method thereof

    JP2023075991A

  • Fuel electrode material for solid oxide type fuel battery, manufacturing method for the same, half cell for solid oxide type fuel battery and single cell for solid oxide type fuel battery having the same

    JP2016071983A